2020
DOI: 10.1186/s12882-020-02152-6
|View full text |Cite
|
Sign up to set email alerts
|

Left-ventricular diastolic dysfunction in Korean children with chronic kidney disease: data from the KNOW-Ped CKD study

Abstract: Background Cardiovascular disease (CVD) is the most common cause of mortality in pediatric chronic kidney disease (CKD) patients. Left ventricular (LV) hypertrophy (LVH) is associated with LV diastolic dysfunction (LVDD) development and is used as an early marker of CVD in pediatric CKD. This study aimed to assess the prevalence and risk factors of LVDD and the association between LVH and LVDD in Korean pediatric CKD patients. Methods Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Second, as the formal definition of LVDD requires additional echocardiographic measures other than E/e ′ (19), the definition of LVDD in this study (i.e., E/e ′ > 14) is a simplified and modified one. Nevertheless, E/e ′ is a feasible and reproducible index to assess the LV filling pressure (19,33) and has been used to evaluate LVDD in the other cohort studies (9,34,35). Third, due to the operational definition of LVDD in this study, the grade of LVDD was not assessed.…”
Section: Limitationsmentioning
confidence: 94%
“…Second, as the formal definition of LVDD requires additional echocardiographic measures other than E/e ′ (19), the definition of LVDD in this study (i.e., E/e ′ > 14) is a simplified and modified one. Nevertheless, E/e ′ is a feasible and reproducible index to assess the LV filling pressure (19,33) and has been used to evaluate LVDD in the other cohort studies (9,34,35). Third, due to the operational definition of LVDD in this study, the grade of LVDD was not assessed.…”
Section: Limitationsmentioning
confidence: 94%
“…Anemia is a common complication of CKD and is asso ciated with several clinical consequences, including mor tality, cardiovascular morbidity, and growth failure 40,41) . Two prospective cohort studies for children with CKD showed that 40%-45% of patients had anemia and the he moglobin level decreases as GFR declines 42,43) .…”
Section: Anemiamentioning
confidence: 99%